Assessing the Relationship Between Work Stress, Feeling Fatigue, and Quality of Life in University Employees - Lalu Muhammad Saleh; Syamsiar S Russeng; Awaluddin Awaluddin; Istiana Tadjuddin; Nurul Mawaddah Syafitri (YCAB Publisher, 2026)
Background: University employees play a crucial role in the academic landscape, which is filled with professional demands. Continuous work pressure poses a risk of affecting their psychological well-being, including overall welfare. In university environment, employees often face high workloads, tight deadlines, and high expectations from supervisors and students. The consequences can affect the quality of life of employees. Objectives: To assess the relationship between psychological fatigue, particularly work stress and feeling of fatigue, and quality of life of employees at Hasanuddin University. Methods: A cross-sectional study with an analytical observational approach was conducted from May to June 2024 at Hasanuddin University's Rectorate in Makassar. The study included 124 employees selected through simple random sampling. Primary data were collected using validated questionnaires: the Work Fatigue Feeling Measurement Tool (KAUPK2) for fatigue, Depression Anxiety Stress Scale 21 (DASS-21) for work stress, and Work-Related Quality of Life (WRQoL) Scale for quality of life. Data analysis employed Spearman correlation and multiple linear regression using Jamovi software version 1.6. Results: The Spearman correlation test revealed a significant negative correlation between work stress and quality of life (ρ = -0.288, p = 0.001), indicating that increased work stress associates with reduced quality of life. Conversely, no significant correlation was found between feelings of fatigue and quality of life (ρ = -0.146, p = 0.106). Multiple linear regression analysis confirmed work stress as a significant predictor of quality of life (β = -0.22, p = 0.020), while feelings of fatigue did not demonstrate significant predictive value (β = -0.13, p = 0.184). Conclusion: Work stress significantly predicts reduced quality of life among administrative employees at Hasanuddin University, while feelings of fatigue show no significant association. These findings underscore the importance of developing targeted stress management interventions within university settings. The study's novelty lies in its focus on administrative staff in Indonesian higher education, providing foundational evidence for institutional health policies. Future research should employ longitudinal designs across multiple institutions to enhance generalizability. Keywords: University Employees; Work Stress; Feeling of Fatigue; Quality of Life